2016
DOI: 10.11138/mltj/2016.6.2.248
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of proximal hamstring tendinopathyrelated sciatic nerve entrapment: presentation of an ultrasound-guided �Intratissue Percutaneous Electrolysis� application

Abstract: SummaryBackground: Proximal Hamstring Tendinopathyrelated Sciatic Nerve Entrapment (PHTrSNE) is a neuropathy caused by fibrosis interposed between the semimembranosus tendon and the sciatic nerve, at the level of the ischial tuberosity. Methods: Ultrasound-guided Intratissue Percutaneous Electrolysis (US-guided EPI) involves galvanic current transfer within the treatment target tissue (fibrosis) via a needle 0.30 to 0.33 mm in diameter. The galvanic current in a saline solution instantly develops the chemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Furthermore, it acts to inhibit the action of IL-1, TNF and COX-2, mechanisms of tendon degeneration through the direct inhibitory action of factor NFKB that facilitates phagocytosis and tendon regeneration (Abat et al 2014 ). The effectiveness of USGET in combination with eccentric exercises has been demonstrated in recent studies (Abat et al 2015 , Abat et al 2016 ; Mattiussi and Moreno, 2016 ; Moreno et al 2017 ).
Fig.
…”
Section: Treatment Optionsmentioning
confidence: 88%
“…Furthermore, it acts to inhibit the action of IL-1, TNF and COX-2, mechanisms of tendon degeneration through the direct inhibitory action of factor NFKB that facilitates phagocytosis and tendon regeneration (Abat et al 2014 ). The effectiveness of USGET in combination with eccentric exercises has been demonstrated in recent studies (Abat et al 2015 , Abat et al 2016 ; Mattiussi and Moreno, 2016 ; Moreno et al 2017 ).
Fig.
…”
Section: Treatment Optionsmentioning
confidence: 88%
“…However, it has also been indicated that longterm randomized controlled trials are needed to demonstrate that this benefit persists over time (29). Additionally, it has been mentioned that applying percutaneous electrolysis under ultrasound guidance would provide maximum precision while minimizing damage to other structures (30). Although articles on this topic initially began to be published in 2010, the increasing number of studies resulted in the highest number of articles entering the list between 2020 and 2023.…”
Section: Discussionmentioning
confidence: 99%
“…Moderate quality evidence supports a positive effect of percutaneous needle electrolysis for reducing pain and related-disability in chronic pain conditions of musculoskeletal origin [12]. In fact, percutaneous needle electrolysis can be applied to different tissues such as tendons [13], muscles [14], or nerves [15]. Further, this intervention has been advocated for managing scars or connective tissue at different interphases, e.g., hamstring tendon-sciatic nerve [14].…”
Section: Introductionmentioning
confidence: 99%